NUMERASI DAN PENELITIAN KOMUNIKASI PENDEKATAN KUANTITATIF - Imran, Hasyim Ali (Istek Widuri Jakarta, 2015)
The quantitative approach research, include in communication science, have been followed principles of positivistic paradigm. This paradigm’s assumption that natural phenomenon and human life social can be numerical scientifically. Basically, the data in quantitative research come from dari René Descartes’ philosophy, namely a priori philosophy.Because of it, this article pays attention to numerical problem in quantitative approach. In fact, the numerical of quantitative data gets many assistance from statistics science to reach meaning of quantitative data. The data processing and analysis with statistics assistance has scientific order. The purpose of strictly using in scientific order is to get a valid research result.